Inovasi Media Pembelajaran Interaktif untuk Meningkatkan Kesadaran Lingkungan di Sekolah dalam Pemilahan Sampah organik dan anorganik di Desa Penanggungan - Hizkia Ananda Putri; Mahimma Romadhona (Jurnal Pelayanan dan Pengabdian Masyarakat Indonesia, 2023)
The Bina Village program is a learning activity for students to jump directly in the community. The activity requires students to contribute actively and creatively to partners. This community service activity is the education of garbage sorting for 1st grade students in Penangungan SDN, Trawas District, Mojokerto Regency. This community service activity involves 31 students and is carried out through two methods, namely board game socialization and 2D animation video viewing. The first stage, students are asked to watch interactive animated videos depicting organic and inorganic waste management. The content of this 2-dimensional animated video includes the definition of garbage, the impact of garbage collection, the types of garbage with color symbols to identify the type of garbage, and the benefits of garbage sorting. The second stage, students are involved in board games. The main focus of the material given is the sorting of organic and inorganic wastes. This is in line with the Adiwiyata program of the school, which is a caring and environmentally cultured school, and has a real program to integrate environmental preservation. Students contribute to creating educational and training facilities to develop students' motor and memory for waste sorting materials. This is expected to form an environmental awareness for students early on, encourage the behavior of the surrounding community in terms of garbage sorting, and preserve the environment for the future through recycling of garbage.